Microplastics in seawater and two sides of the Taiwan Strait: Reflection of the social-economic development. (August 2021) - Wu, Qianqian; Liu, Siguang; Chen, Piao; Liu, Mengyang; Cheng, Sha-Yen; Ke, Hongwei; Huang, Peng; Ding, Yongcheng; Cai, Minggang
Abstract: Microplastic abundance, distribution and source characteristics were investigated for the surface seawaters from the Taiwan Strait as well as those of sediments along its west and east coasts. The microplastic abundances were in the range of 28–208 (mean 90) and 10–246 (mean 69) items/kg (d.w.) along the west and east coasts respectively. The higher microplastic abundance on the west coast might be related to the different local economic development, population, land-use and other human activities. Combined with microplastic pollution and socio-economic development, regression analysis results showed that urbanization level is negatively correlated with foams while positively correlated with fibers. This study, as the first report of microplastics in the Taiwan Strait, suggested further research on microplastics cross-strait transportation and the relationship with economic developments. Graphical abstract: Unlabelled Image Highlights: Microplastics were investigated in seawater and two sides of the Taiwan Strait. Distinction on microplastic shapes indicated their input and settling conditions. Microplastic levels reflected multiple socio-economic developments. Urbanization level was negatively correlated with plastic foams.